Drag Forces under Longitudinal Interaction of Two Particle - H. Sulaymon, Abbas; A. M. Mohammed, Sawsan (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
Direct measurements of drag force on two interacting particles arranged in the longitudinal direction for particle Reynolds numbers varying from J O to 103 are conducted using a micro-force measurement system. The effect of the interparticle distance and Reynolds number on the drag forces is examined. An empirical equation is obtained to describe the effect of the interparticle distance (l/d) on the dimensionless drag.